Mangrove development and its response to environmental change in Yingluo Bay (SW China) during the last 150 years: Stable carbon isotopes and mangrove pollen. (August 2015) - Xia, Peng; Meng, Xianwei; Li, Zhen; Feng, Aiping; Yin, Ping; Zhang, Yongqiang
Highlights: Contribution of mangrove Corg to sediments calculated via a mixing model from δ 13 Corg and C:N. Mangrove evolution reconstructed from mangrove-derived Corg and mangrove pollen. Temperature may be a key factor for short term mangrove development. Abstract: Located at the interface of terrestrial and marine ecosystems, mangroves are particularly sensitive to environmental change. They provide a sedimentary sink for organic carbon, whereby cores can provide detailed records of mangrove species. We aimed to trace the history of mangrove development over the past 150 years in Yingluo Bay, SW China. Sedimentation rates (avg. 0.32 and 0.37 cm/year) were calculated on the basis of ln( 210 Pbex ) vs. mass depth, and offset the rate of relative sea level rise (0.22–0.24 cm/year), leading to a seaward expansion of new mangrove habitats. Chemical tracers (δ 13 Corg and C:N) and an isotope mixing model were utilized to trace the contribution of mangrove-derived organic matter (MOM). Changes in the relative abundance of pollen from mangrove plants was used to compensate for diagenetic alteration of the stable isotope values and potential overlaps in isotope values for different sources of organic matter. The result of Pearson correlation analysis showed that the MOM was moderately positive correlated with total mangrove pollen, indicating that stable carbon isotopes and mangrove pollen provide similar information for tracing mangrove ecosystems. Based on results from this study, compositional changes in mangrove communities could be divided into two main stages: a degradation period (1870–1930 AD) and a flourishing period (1930–2011 AD), corresponding to colder temperature and warmer temperature, respectively. Owing to the location being far away from any industrial area and human activity, temperature may be a key factor for mangrove development.